Fejezetek a huszonötéves krakkói magyar szak történetéből - Nagy, László (Gerundium, 2016)
ASPECTS PERTAINING TO THE TWENTY-FIVE-YEAR HISTORY OF THE HUNGARIAN ACADEMIC PROGRAM AT CRACOW. This study, which also encompasses present-day events, commemorates the fact that in the academic year of 2014/2015 the Department of Hungarian Philology, Jagello University, Cracow, celebrated the twenty-ifth anniversary of its existence. he reader is ofered an insight into the struggles and events in the wake of the establishment of the Department in 1988, as well as into the cultural mission that has guided the Department in maintaining Polish-Hungarian relations. Not suppressing the theme of attendant diiculties, the text radiates a substantial sense of mission and hope, while the author highlights the professional Hungarian program as well as the research activity of the academic staf that has made these projects – and ideas pertaining to the future a realiy.